EFFICACY OF COMBINED ANTIHYPERTENSIVE THERAPY IN ACHIEVEMENT OF TARGET BLOOD PRESSURE IN DIABETIC PATIENTS - O. A. Koshel'skaya; O. A. Zhuravleva; R. S. Karpov (Столичная издательская компания, 2015)
Aim. To evaluate the efficacy of long-term combined antihypertensive therapy (AHT) based on renin-angiotensin-aldosterone system (RAAS) blockers, indapamide and calcium channel blocker (CCB) in hypertensive patients with diabetes mellitus (DM) in accordance with target blood pressure (BP) <130/80 mm Hg achievement rate, dynamics of 24-hour BP profile, metabolic indices, and local stiffness of the main arteries. Besides, to study the effects of the CCB addition to dual therapy on these parameters. Material and methods. Patients (16 men, 31 women, 57.2±6.6 years old) with arterial hypertension degrees 1-3 and mild to moderate DM type 2 were included into the study. The patients were treated with perindopril (5-10 mg/day) or valsartan (80-160 mg/day) in combination with indapamide SR (1.5 mg/day) and amlodipine (5-10 mg/day). Examination included office BP measurement and ambulatory BP monitoring (ABPM), common carotid arteries sonarography , evaluation of serum levels of potassium, creatinine, uric acid, glucose metabolism and lipid profile parameters, calculation of insulin resistance index (HOMA) at baseline and after 30-32 weeks of treatment. Results. Target BP was achieved in 86.7% of patients. Evenly reduction of day and night BP without reflex tachycardia and hypotension episodes was observed. Office BP decreased from 149.5±12.0/90.0±8.3 to 125.0±7.6/76.8±4.9 mm Hg (p<0.05) and average daily BP (ABPM) decreased to 120.1±10.0/71.7±6.9 mmHg. Three drugs were needed to achieve target BP in baseline systolic BP >150 mm Hg (office) or >134 mmHg (ABPM). Marked beneficial effect on the morphological and functional characteristics of the vascular wall and its elastic properties, improvement of glycemic control, tissue insulin sensitivity and lipids profile were found. These effects were associated mainly with amlodipine inclusion into the therapy. Conclusion. The combined AHT based on RAAS blockers, indapamide SR and CCB provides achievement of target BP in the most of hypertensive patients with DM and accompanied by positive changes in vascular remodeling and metabolism.